2011
DOI: 10.1590/s1807-59322011000500008
|View full text |Cite
|
Sign up to set email alerts
|

Minichromosome maintenance 2 and 5 expressions are increased in the epithelium of hereditary gingival fibromatosis associated with dental abnormalities

Abstract: INTRODUCTION:Gingiva fibromatosis is a relatively rare condition characterized by diffuse enlargement of the gingiva, which is caused by expansion and accumulation of the connective tissue.OBJECTIVE:The aim of the present study was to investigate proliferative and apoptotic biomarker expression in normal gingiva and two forms of gingival fibromatosis.METHODS:Archived tissue specimens of hereditary gingival fibromatosis, gingival fibromatosis and dental abnormality syndrome and normal gingiva were subject to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…We have also previously reported that the pathogenesis of gingival overgrowth involves the inhibition of apoptosis mediated by the down‐regulation of Bax, caspases (3, 8 and 9), p53 and cytochrome c and the overexpression of Bcl‐2 (Takeuchi et al, ). Increased expression levels of minichromosome maintenance (MCM) protein subunits 2 and 5 have been found in cases of gingival fibromatosis and are associated with dental abnormalities (Martelli‐Júnior et al, ). In this study, we investigated the effects of 18α‐GA on the expression of cyclins (A, D1 and E), CDKs (2, 4 and 6), Rb, pRb (ser 780 and ser 807/811 ), p27 Kip1 , Bcl‐xL, Bcl‐2, cytochrome c (total and cytosolic), and p53 and the activities of caspase‐2, caspase‐3, caspase‐8 and caspase‐9.…”
Section: Discussionmentioning
confidence: 99%
“…We have also previously reported that the pathogenesis of gingival overgrowth involves the inhibition of apoptosis mediated by the down‐regulation of Bax, caspases (3, 8 and 9), p53 and cytochrome c and the overexpression of Bcl‐2 (Takeuchi et al, ). Increased expression levels of minichromosome maintenance (MCM) protein subunits 2 and 5 have been found in cases of gingival fibromatosis and are associated with dental abnormalities (Martelli‐Júnior et al, ). In this study, we investigated the effects of 18α‐GA on the expression of cyclins (A, D1 and E), CDKs (2, 4 and 6), Rb, pRb (ser 780 and ser 807/811 ), p27 Kip1 , Bcl‐xL, Bcl‐2, cytochrome c (total and cytosolic), and p53 and the activities of caspase‐2, caspase‐3, caspase‐8 and caspase‐9.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity can be illustrated by several examples, such as the study of Sullivan et al (20), in which genetic sequencing uncovered a mutation in the gene responsible for amelogenesis imperfecta FAM20A associated with GF. Another example is the increased minichromosome maintenance 2 and 5 expression in the epithelium of hereditary gingival fibromatosis associated with dental abnormalities compared with non-syndromic forms of HGF (21). Studies have addressed the use of Hsp47 as a biomarker in cancer (22) and fibrotic diseases (23,24), given the intimate relationship of this protein with the excessive accumulation of collagen, a feature that is present in HGF.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity can be illustrated by several examples, such as the study of Sullivan et al (20), in which genetic sequencing uncovered a mutation in the gene responsible for amelogenesis imperfecta FAM20A associated with GF. Another example is the increased minichromosome maintenance 2 and 5 expression in the epithelium of hereditary gingival fibromatosis associated with dental abnormalities compared with non-syndromic forms of HGF (21). Studies have addressed the use of Hsp47 as a biomarker in cancer (22) and fibrotic diseases (23,24), given the intimate relationship of this protein with the excessive accumulation of collagen, a feature that is present in HGF.…”
Section: Discussionmentioning
confidence: 99%